The great ABC book of the samogitians and Lithuania by A. Bendikas (1867– 1939) is the source of arithmetic basics - Banionis, Juozas (Lietuvos matematikos rinkinys, 2012)
A. Bendikas is the great book spreader, the publisher of Lithuanian calendars, a teacher in secret Lithuanian schools. In 1906, A. Bendikas published “The ABC book” which is different from other similar works by paying attention to the development of arithmetic basics. The book was not designed only to familiarization with Arabic, Roman numerals and multiplication table but it also presented the teaching of all four arithmetic operations. In familiarizing with four arithmetic operations, the emphasis was put on the method of purposeful tasks and oral tasks which fostered logical mastering of operations and developed students’ thinking.
Keywords: the ABC book; number; arabic and Roman figure; four arithmetic operations